Factors Affecting College Choice of African American Male Undergraduates at Two Private Liberal Arts Colleges in the South - Cook, Louis L.; Okojie, Felix A. (Advances in Social Sciences Research Journal, 2024)
This article examined the factors influencing the college choice of African American male undergraduate students at two private liberal arts colleges in the South. Utilizing Hossler and Gallagher's (1987) College Choice Model as the theoretical framework, the study explored these students' experiences, perceptions, and attitudes toward the college selection process. The research investigated explicitly how predisposition, search, and choice factors impact the decision-making process for African American males at these institutions. Employing a qualitative methodology, data were collected through in-depth interviews with 20 participants. The findings revealed that family and community influences, financial considerations, campus environment, and diversity significantly shape college choice. The study contributes to a deeper understanding of the factors affecting college choice for African American males at private liberal arts colleges in the South. Additionally, it offers insights that could inform the development of policies and practices to enhance access, diversity, and educational equity within higher education.